Tubercular pyometra in a young unmarried female - dilemma and pitfalls in diagnosis: a rare case report with review of literature - Aggarwal, Rasika; Malik, Renuka; Singh, Swati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
This rare case is the first case being reported as tubercular pyometra in a young unmarried woman. Diagnosis of genital tuberculosis which is a form of EPTB (extra pulmonary TB) can be baffling, compelling a high index of suspicion owing to paucibacillary load in the biological specimens. A negative smear for acid-fast bacilli, lack of granuloma on histopathology and failure to culture mycobacterium tuberculosis do not exclude the diagnosis of EPTB. A 25-year-old unmarried, government employee from Bihar presented to our OPD with secondary amenorrhea for two months carrying with her an USG, CT and MRI done in Bihar suggesting enlarged uterus with fluid collection. CT-also reported few enlarged lymph nodes. Her preoperative investigations revealed an elevated ESR and x-ray chest was normal. Dilatation was done under ultrasonic guidance in OT and 150 cc of thick caseous material was drained A gentle curettage was done on lateral wall near cornea and both the caseous material and endometrial tissue was sent for gram staining, TB-PCR (polymerase chain reaction), NAAT (nucleic acid amplification techniques) and culture. In the post-operative period gram staining for AFB, NAAT, TB-PCR all came negative and it was difficult to convince patient to take ATT. However, on day 10, HPE report came as granuloma suggestive of TB and patient was put on ATT. Culture too was reported negative later. Paucibacillary female genital TB (FGTB) is difficult to diagnose because of varied presentation and limitations of diagnostic tests A raised ESR is presumptive but non-specific. Other tests are x-ray chest, HSG, endometrial tissue for TB PCR nucleic acid amplification techniques (NAAT, HPE and culture (conventional or Bactec). Patients with EPTB are, however, more likely to have negative sputum smear results and many EPTB cases do not have direct lung involvement. Currently, there are no standard guidelines or algorithm for the diagnosis of FGTB. Female genital TB has varying presentation and diagnosis is difficult because of the paucibacillary nature.